Simulações de onda de cheia na sub-bacia do Ribeirão Claro - SP - Silva, Raquel Reis Pontes e [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Watersheds are considered important study units when it comes to environmental planning, with regard to the optimal use of water resources. Water scarcity is predicted and feared by many societies, and proves to be an increasingly tangible problem nowadays. Still from the perspective of extreme events, this dissertation considers the study of flood waves in the sub-basin of the stream Claro, which belongs to the Corumbataí watershed. - SP, since thay can also have devastating effects for the population, A Decision Support System for Flood Routing Analysis in Complex Basins, ABC 6 software was applied in order to obtain hydrographs and peak flows in the sub-basin of the stream Claro, for return periods of 10 and 100 years, aiming to comprise events of different magnitudes. The model Soil Conservation Service (SCS) and the triangular SCS hydrograph were adopted for the simulations. Simultaneously, the Kokei Uehara method was applied for the obtainment of peak flow values under the same conditions, seeking to compare results. Data collection was performed using geoprocessing tools. For data entry in ABC 6, the fragmentation of sub-basin of the stream Claro was necessary, which generated 7 small watersheds, in order to fulfill a software demand, as the maximum drainage area it accepts is 50km² for each watershed analyzed. For RT = 10 and 100 years, respectively, the results of peak flow with use of ABC 6 were 46.10 and 95.45 m³/s, while for Kokei Uehara method, the results were 47.17 and 65.26 m³/s. The adoption of a single value of discretization time for all watersheds was indicated as limitation of ABC 6, which interfered in the final results. Kokei method Uehara considered the sub-basin of the stream Claro as a whole, which reduced the error accumulation probability

Bacias Hidrográficas são consideradas importantes unidades de estudo e planejamento ambiental, no que diz respeito à otimização do uso de recursos hídricos. A escassez de água é prevista e receada por muitas sociedades, e revela-se um problema cada vez mais tangível nos dias de hoje. Ainda sob a ótica dos eventos extremos, o presente trabalho leva em consideração o estudo de ondas de cheia na sub-bacia do ribeirão Claro, pertencente à bacia do rio Corumbataí - SP., que podem ter efeitos igualmente devastadores para a população, Um Sistema de Suporte de Decisões para Análise de ondas de Cheia em Bacias Complexas, o software ABC 6, foi aplicado para obtenção de hidrogramas e vazões de pico na sub-bacia do ribeirão Claro para os períodos de retorno (TR) de 10 e 100 anos, visando contemplar eventos de diferentes magnitudes. Foi adotado o modelo Soil Conservation Service (SCS), e o hidrograma triangular do SCS para as simulações. Paralelamente, foi empregado o Método Kokei Uehara para a obtenção de vazões de pico nas mesmas condições, buscando a comparação de resultados. A coleta de dados foi realizada por meio de ferramentas de geoprocessamento. Para a inserção de dados no ABC 6, foi necessária a fragmentação da sub-bacia do ribeirão claro em outras 7 microbacias, buscando cumprir uma demanda do software quanto ao valor de área de drenagem máxima de 50km² por microbacia analisada. Para TR=10 e 100 anos, respectivamente, os resultados das vazões de pico com uso do ABC 6 foram 46,10 e 95,45 m³/s, enquanto para o Método Kokei Uehara, os resultados foram 47,17 e 65,26 m³/s. A adoção de um único valor de discretização temporal para todas as microbacias foi indicada com uma limitação do ABC 6, o que interferiu nos resultados finais. Já o Método Kokei Uehara, considerou a sub-bacia do ribeirão Claro como um todo, o que provavelmente reduziu as possibilidades de acúmulo de erros
Keywords: Sistema de Suporte a Decisões para Análise de Ondas de Cheia em Bacias Comlexas (Programa de computador); Hidrologia; Tecnologia; Bacias hidrograficas; Ribeirão Claro, Bacia (SP)